2021
DOI: 10.3390/ph14101031
|View full text |Cite
|
Sign up to set email alerts
|

The Cross Talk between Underlying Mechanisms of Multiple Sclerosis and Epilepsy May Provide New Insights for More Efficient Therapies

Abstract: Despite the significant differences in pathological background of neurodegenerative diseases, epileptic seizures are a comorbidity in many disorders such as Huntington disease (HD), Alzheimer’s disease (AD), and multiple sclerosis (MS). Regarding the last one, specifically, it has been shown that the risk of developing epilepsy is three to six times higher in patients with MS compared to the general population. In this context, understanding the pathological processes underlying this connection will allow for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 192 publications
(216 reference statements)
0
3
0
Order By: Relevance
“…Myelin is constantly produced in the adult brain by oligodendrocytes in a plasticity-dependent manner and necessary for memory consolidation (Steadman et al, 2020). Myelination deficiencies have been found in several neurologic disorders in particular in multiple sclerosis (Nave and Werner, 2014) and are often associated with seizure occurrence (Rayatpour et al, 2021). There is increasing awareness that also in epilepsy maladaptive myelination or axon demyelination are of high relevance for seizure generation (De Curtis et al, 2021, Knowles et al, 2022.…”
Section: Discussionmentioning
confidence: 99%
“…Myelin is constantly produced in the adult brain by oligodendrocytes in a plasticity-dependent manner and necessary for memory consolidation (Steadman et al, 2020). Myelination deficiencies have been found in several neurologic disorders in particular in multiple sclerosis (Nave and Werner, 2014) and are often associated with seizure occurrence (Rayatpour et al, 2021). There is increasing awareness that also in epilepsy maladaptive myelination or axon demyelination are of high relevance for seizure generation (De Curtis et al, 2021, Knowles et al, 2022.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in the context of MS, seizures may exacerbate demyelination, reflecting the fact that the two diseases share some common pathophysiology. Understanding the pathological processes underlying this relationship will allow us to target common and shared pathological pathways associated with both diseases, which may lead to new approaches to the treatment of these neurological disorders [33].…”
Section: Age and Gender Characteristicsmentioning
confidence: 99%
“…As it was determined in a retrospective study of the Swedish population registry, which included 514, 545 patients with MS, the incidence of epilepsy grew with the increase in the duration and severity of the major disease, with its progressive course, and was dependent on the effect of drug therapy for MS [31]. In addition to MS, several studies have reported seizures in other demyelinating disorders, such as myelin oligodendrocyte glycoprotein antibody-associated disease (MOGAD) and progressive multifocal leukoencephalopathy [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…The distribution of MS lesions may be related to cognitive impairment, recurrent seizures, or status epilepticus (90). Cortical or juxtacortical lesions have been found to be a precipitating factor for epileptic seizures in patients with MS in multiple studies (91,92).…”
Section: The Role Of Imagistic Techniques In Studying the Ms-epilepsy...mentioning
confidence: 99%